1995
DOI: 10.1038/bjc.1995.371
|View full text |Cite|
|
Sign up to set email alerts
|

Functional detection of MDR1/P170 and MRP/P190-mediated multidrug resistance in tumour cells by flow cytometry

Abstract: Summary Multidrug resistance (MDR) in tumour cells is often caused bv the overexpression of the plasma membrane drug transporter P-glycuprutein (P-gp) or the recently discosered multidrug resistance-associated protein (MRP). In this studs we insvestigated the specificity and sensitivity of the fluorescent probes rhodamine 123 (R123). daunorubicin (DNR) and calcein acetoxymethvl ester (calcein-AM) in order to detect the function of the drug transporters P-gp and MRP. using flow cytometrv. The effects of modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
79
0
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 25 publications
2
79
0
2
Order By: Relevance
“…We have quantified the N/C ratio by fluorescence 833). 1,31 In the latter case, the cells cannot be loaded with dye in the presence of the modulator if subsequently the laser scan microscopy in MDR cell lines and shown that it correlates with resistance even in very low resistant tumor cell dye efflux is to be studied. 1 (6) Finally, one has to be aware that the protein concentration lines.…”
Section: Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have quantified the N/C ratio by fluorescence 833). 1,31 In the latter case, the cells cannot be loaded with dye in the presence of the modulator if subsequently the laser scan microscopy in MDR cell lines and shown that it correlates with resistance even in very low resistant tumor cell dye efflux is to be studied. 1 (6) Finally, one has to be aware that the protein concentration lines.…”
Section: Cellsmentioning
confidence: 99%
“…10 For the combination A double labelling procedure with R123 and FITC labels is impossible and the combination with PE label still requires R123/PSC833, it is short-term accumulation that provides Pgp specificity. 1,27 Since some MRP-overexpressing cell extensive compensation. 25 For that reason, the procedure of Leith et al 17 who used DiOC 2 (3) combined with PE-labelled lines respond to PSC833, its Pgp specificity is not absolute.…”
mentioning
confidence: 99%
See 3 more Smart Citations